An experimental study of the seismic behaviour of precast concrete shear walls with bolted-plate connections. (1st December 2021) - Pan, Guang-Bin; Cai, Jian; He, An; Chen, Qing-Jun; Zuo, Zhi-Liang; He, Bing-Quan; Tang, Xu-Lin; Wu, Hong-Wei
Highlights: An innovative precast reinforced concrete shear wall with bolt-plate connection was proposed. Horizontal cyclic loading tests on the precast walls were conducted. The seismic performance of the precast walls was examined. Design methods for the precast shear walls were proposed. Abstract: The seismic resistance of an innovative precast reinforced concrete shear wall with vertical plates along its bottom edge to be bolted to plates protruding from the foundation was tested in reduced-scale model in the laboratory. Five precast shear walls with different wall heights and axial loads, as well as one reference cast-in-place shear wall, were tested. Horizontal cyclic loading was applied to examine the seismic performance of the specimens. The failure modes of the shear walls are discussed, along with their hysteretic behaviour, stiffness degradation, energy dissipation capacity, slip at the bolted connections, and strains in the reinforcement and in the connecting plates. The test results show that the bolted-plate connections can effectively transfer vertical and shear forces, as well as bending moments, to the foundation beam without any slip along the connection. The precast specimens exhibited approximately the same seismic behaviour as the cast-in-place one. In general, the failure mode shifts from compression-bending to shear-compression at smaller heights of the walls, with an increase in the bearing capacity, but a reduction in wall deformability and the energy-dissipation capability. At smaller values of the axial loads, the bearing capacity decreases but the deformability increases. The existing Chinese design code for normal reinforced concrete shear walls gives safe design limits also for the precast walls with bolted-plate connections.